Health economic analysis: What do we need to know? (Research, Society and Development, 2021)
In the Health Technology Assessment (HTA), economic evaluations assessments are constantly used, as they are analysis techniques that comparatively assess two or more technologies/programs/actions through the systematic measurement of costs and their consequences. The aim of the article is to illustrate how the basic principles of health economics can be applied to decision-making in health through analysis techniques that provide information so that the allocation of resources is rational and transparent in times of budget constraints. This is becoming increasingly important as the demand for healthcare services increases and so do the costs associated with treatment. This article presents general definitions of economic valuation analysis techniques; It describes the main comprehensive economic assessments: cost-effectiveness, cost-utility, cost-minimization, and cost- effectiveness, provide information to be used to determine the best course of action, where the choice and use of health technologies can be prioritized.